2015
DOI: 10.5387/fms.2015-18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of L-Menthol in the Upper Gastrointestinal Endoscopic Procedure

Abstract: : Aim : Peppermint oil, which suppresses gastric peristalsis during esophagogastroduodenoscopy (EGD), is effective for determining the margin of a gastric tumor. This study was conducted to evaluate the utility of an L -menthol preparation for suppressing gastric peristalsis and for diagnosing gastric tumors. Methods : The study examined 124 patients who underwent EGD between January and April 2012. After 20 mL of 0.8% L -menthol was sprayed directly onto the mucosal surface of the gastric antrum, the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…As regards tumor location, trainees missed the lesions in the lower or lesser curvature of the stomach compared with experienced endoscopists. We speculated that insufficient air insufflation and poor upside angulation were attributed to a high miss rate in the lesser curvature, and poor observation due to gastric peristalsis might result in missing EGCs in the lower stomach [ 29 ]. EGCs in the posterior wall are difficult to detect because of the tangential endoscopic vision to the posterior wall [ 30 ]; however, no significant difference in detection rates was noted.…”
Section: Discussionmentioning
confidence: 99%
“…As regards tumor location, trainees missed the lesions in the lower or lesser curvature of the stomach compared with experienced endoscopists. We speculated that insufficient air insufflation and poor upside angulation were attributed to a high miss rate in the lesser curvature, and poor observation due to gastric peristalsis might result in missing EGCs in the lower stomach [ 29 ]. EGCs in the posterior wall are difficult to detect because of the tangential endoscopic vision to the posterior wall [ 30 ]; however, no significant difference in detection rates was noted.…”
Section: Discussionmentioning
confidence: 99%
“…10 Antiperistaltic and antispasmodic effects of peppermint oil or L-menthol have been studied in several trials. [11][12][13] Japanese researchers have confirmed that L-menthol could improve the stability of the visual field both in endoscopic diagnosis and treatment, including gastric endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD), [14][15][16] thereby making it a useful antispasmodic drug for upper GI endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Spraying peppermint oil [14,15] or L-menthol [16,17] onto the gastric mucosa during endoscopic procedure has been shown to suppress gastric peristalsis. Moreover, we have explored the benefits of peppermint oil or L-menthol in the endoscopic identification and margin determination of EGC [17,18]. Mori et al [19] have also reported that spraying L-menthol mixed with indigo carmine onto lesions allowed clear visualization of the margins of gastric lesions.…”
Section: Introductionmentioning
confidence: 99%